Muhammad in The West: Analysis of the Historical Description of the Prophet Muhammad in Armstrong’s Writings - Masmuni Mahatma (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
The main objectives of this study are to analyze and understand: (1) the general constructions of the Prophet Muhammad in the descriptions of Western writers; and (2) Armstrong's description of the Prophet Muhammad. This study is library research that uses a qualitative approach with a descriptive-critical method. Data were collected by reading various biographical literature on Prophet Muhammad from Western writers, which were grouped into three criteria: orientalist writers, revisionist writers, and popular writers. The results of the study show that: (1) there is a dynamic dialectic in the description of the figure of the Prophet Muhammad by Western writers, both from orientalist circles, such as W. Montgomery Watt, David Samuel Margoliouth, Edward Said, revisionists such as Patricia Crone, Michael Cook, Fred M. Donner, and popular writers like Karen Armstrong. This dynamic shows that the effort to understand the figure of the Prophet Muhammad is an important effort to understand Islam in Western society; and (2) Armstrong's description as the author of popular religious studies books about the figure of the Prophet Muhammad; made a major contribution to reducing various misunderstandings about Islam and the figure of the Prophet Muhammad in the eyes of Western society.